Linking neighborhood food environments to dietary habits in rural South Asia: Fruit, vegetables (F&V) and ultra-processed food (UPF) consumption - Choudhury, Samira; Afrin, Zainab Bi; Faijul Kabir, A.N.M.; Veettil, Prakashan Chellattan (TAFSSA, 2024)
TAFSSA (Transforming Agri food Systems in South Asia), a CGIAR regional integrated initiative, addresses food system challenges by delivering actionable evidence and scalable innovations in South Asia. This brief offers an overview of linkages between rural food environments and consumption of fruits, vegetables and ultra-processed foods in Bangladesh and India. The findings can assist policymakers in redesigning food environments to promote the availability of healthy foods and monitor the sales of unhealthy products.